UPAYA MENINGKATKAN KUALITAS LAYANAN PUBLIK MELALUI DIGITALISASI (STUDI KASUS DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA PALEMBANG) - Ignasius Hendrasmo; Akhmad Muftizar (AS-SIYASAH : Jurnal Ilmu Sosial Dan Ilmu Politik, 2024)
Digitalization means the use of science and technology in the implementation of government both at the central and regional levels, especially public services to the community. Palembang city is one of the major cities in Indonesia that has carried out digitalization of public services. This can be seen in one of the service agencies in the Investment Office and One Door Integrated Service (DPMPTSP) of Palembang City with the real form of a Public Service Mall. Based on this, the author is interested in researching How the Palembang City Government Strives to Improve the Quality of Public Services Through Digitalization. The results of research obtained based on the characteristics of the quality of public services, namely the existence of tangibles, reliability, responsiveness, assurance, and empathy can be concluded DPMPTSP Palembang city has implemented it optimally. This study uses qualitative research methods that emphasize the results of observations and interviews of various parties related to the formulation of the problem. This research is expected to make an important contribution to the progress of public services in Palembang City, furthermore this research supports.